Representasi Nilai Ekologi dalam Cerpen Muna Masyari: Analisis Ekokritik - Moh Rizal Ali; Bahruddin Bahruddin (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The representation of ecological values ​​in short stories is the way the work depicts the relationship between humans and nature. This includes how nature is depicted, the values ​​given to nature, as well as how humans act towards nature. The aim of this research is to explain the relationship between humans and nature, namely the way the characters in short stories interact with their environment. The short stories analyzed are Tumbal Suramadu, and Sumur by the Madurese writer Muna Masyari. The method applied is qualitative with note-taking techniques. Data analysis was carried out in three stages (1) recording data that was considered important related to ecocriticism; (2) presenting and arranging the data so that describing the data obtained is easy to understand; (3) drawing conclusions and adjusting data. Based on the results of the analysis, there are two points in the short story, namely regarding preserving and loving nature and rejecting natural exploitation